Effects of Total Western Diet and Wheat Class and Fraction on Preneoplastic Colon Cancer Risk. (7th June 2021) - Bailey, Allison; Gallaher, Daniel; Simsek, Senay
Abstract: Objectives: Colon cancer (CC) is a leading cause of cancer-related deaths worldwide and is particularly prevalent among persons consuming a Western-style diet. Red wheat, compared to white wheat, may reduce CC risk, as measured by reductions in colonic preneoplastic lesions (aberrant crypt foci; ACF). Rodent studies typically use a purified diet (AIN-93G) as the background diet, but due to its optimal nutritional composition, it may mask some effects of chemopreventive bioactives. The Total Western Diet (TWD), matched to the 50 th percentile of US diets using NHANES data, has greater translational integrity to humans. This study aims to elucidate effects of background diet (AIN-93G vs TWD), wheat class (red vs white), and wheat fraction (whole vs refined vs testa layer) when fed during the post-initiation period. Methods: Male Wistar rats ( n  = 83) were injected with the colon-specific carcinogen 1, 2-dimethylhydrazine (twice, one week apart) to induce ACF. Five days after final injection, diets containing either AIN-93G or TWD background and various fractions of red and white wheat were fed for 10 weeks. Results: No statistically significant differences in ACF number were found due to background diet. However, a statistically significant decrease in ACF was found in rats fed the TWD + whole red wheat (RW) relative to the TWD and the AIN-93G + refined red wheat diets. The short-chain fatty acid (SCFA) butyrate may act as a histone deacetylase to prevent CC. TWD + RW significantly increased total SCFAs as well as total butyrate compared to all other groups. TWD had significantly decreased total SCFAs and total butyrate compared to AIN-93G. Preliminary immunohistochemical results show that neither beta-catenin (part of the Wnt signaling pathway frequently dysregulated in CC) nor doublecortin-like kinase 1 (DCLK1; a putative cancer stem cell marker) staining of ACF significantly differ between TWD and TWD + RW. Conclusions: The butyrate amount in cecal contents did not correlate with the staining intensity within ACF for beta-catenin or DCLK1 biomarkers, which does not support a role for high total butyrate reducing the risk of CC. Red wheat, when fed as part of the TWD, may reduce CC risk. Funding Sources: Healthy Foods, Healthy Lives Institute, University of Minnesota.